The Relationship between Asia Pacific Markets during the Financial Crisis: VAR-Granger Causality Analysis - Hayun Kusumah; Marwan Asri; Kusdhianto Setiawan; Bowo Setiyono (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This study investigates the relationships between equity markets during the Asian financial crisis and the subprime mortgage crisis in Asia-Pacific. Background Problems: The advantages of market integration are under scrutiny in the midst of global financial crises, which have many implications for international asset pricing and regulators to develop strategies to protect economies. During the crises, the equity markets responded with different patterns, and it is important to understand in more detail the market relations during each crisis, especially for the less and more integrated markets. Novelty: We provide in-depth analysis to compare the market relationships during two extremely different financial crises originating from less integrated markets (i.e., emerging ones) and more integrated markets (i.e., developed ones), based on the prices which give a direct measurement and clear interpretation. This research provides a significant contribution by showing new findings in the form of a comparison of market relations during two extremely different crises in the Asia-Pacific region. Research Methods: This study employs time-series data from economic territories based on the Morgan Stanley Capital International (MSCI) Asia-Pacific classification and the United States. We conducted analysis using the vector autoregressive, Granger causality test, and impulse response, to point out the market relationships during the crises or turmoil periods. Finding/Results: The results show that the Asian financial crisis affected the emerging markets more and this indicates the unidirectional causality relationships among them. Meanwhile, the subprime mortgage crisis affected all the markets, but more indicated the bidirectional relationships, especially the developed markets. Conclusion: Although these two financial crises were global in nature, the effects on the region were different. The origin of the shock and the level of market integration affected the market relationships differently during the crises.